Peran Orang Tua dalam Membentuk Akhlak Anak Sejak Dini - Nur Lailatul Fitri (Universitas Al-Hikmah Indonesia, 2017)
Parents have an important role in shaping the moral valuess of children. But busyness becomes the main reason parents do not have enough time to educate children, consequently education is left entirely to the teacher. The cultivation of moral values from an early childhood becomes an important point to face the moral decadence that occurs, where the family has a major role in shaping the morals of children. The purpose of writing this article is to know the role of parents in shaping the morality of children in Gesik, Gesikharjo village RT / RW 002/002. The methodology of writing this article is descriptive qualitative. Data were collected through observation, interview and documentation, then analyzed by data reduction, data presentation and conclusion. The result of this research is parents in Gesik, Gesikharjo village RT / RW 002/002 who have quality togetherness with children and who apply democratic parenting, they can shape the children’s behaviour rich with moral values.